Degradation of biochemical fractions in different temperature of food waste bioevaporation and their contribution to biogenerated heat. (1st February 2020) - Liu, Yanmei; Hu, Die; Lin, Zhiqiang; Zhou, Xiandong; Peng, Zhenghua; Yang, Benqin; Pan, Xuejun
Abstract: Bioevaporation is a treatment for highly concentrated organic wastewater that uses biogenerated heat from organic matter degradation to remove water from wastewater itself. The degradation of organics is important when investigating bioevaporation process. The aim of this study was to investigate organic compounds degradation in different temperature stages and evaluate their contribution to biogenerated heat during food waste (FW) bioevaporation by using biofilm-developed sponge (BF) as a clean, light and easy-to-prepare bulking agent and microbial carrier. Results showed that amylums were significantly decomposed in all stages and lipids were decomposed a lot except the warming 30 °C to top-temperature stage. Decomposition of amylums and lipids contributed to the main total volatile solids (VS) loss (75.63% and 77.87% in the 1st and 2nd cycle, respectively). Water soluble organic carbon (WSOC) variations were fluctuated especially at the thermophilic phase. The decomposition of hemicellulose (HEM) occurred until cooling 30 °C. However, the degradation of proteins and lignin (LIG) was not significant during the whole process. Carbohydrates and lipids successively served as main substrates for producing biogenerated heat and totally contributed 87.54% and 89.06%, in the 1st and 2nd cycle, respectively. Throughout the process, various organics contained in FW induced extracellular enzymes in different levels, resulting in different degradation performance. The foremost induced enzyme was amylase with activity of 114.50 mg reducing sugar g −1 TS (total solids) min −1 at warming 50 °C of the 2nd cycle, which facilitated amylums to be degraded preferentially. Fluorescence labeling further confirmed significant decrease of amylums and lipids and the slight decrease of proteins. However, decreasing fluorescence intensity of cellulose (CEL) in the top-temperature stage firmly reflected its degradation, which was covered by the content variations caused by readily biodegradable fractions. Graphical abstract: Image 1 Highlights: Decomposition of amylums and lipids accounted for 75.63%–77.87% of the VS loss. 48.75%–55.54% of the biogenerated heat was from the degradation of carbohydrates. Degradation of organic matter was regulated by corresponding enzymes. Amylase was the most active enzyme during the FW bioevaporation with BF. CLSM deeply reflected organic matter distribution and degradation.